OP0136 Microrna-223-3p expression in affected skin of adult iga vasculitis correlates with the severity of skin involvement. (15th June 2017) - Hocevar, A; Pizem, J; Tomsic, M; Glavac, D
Abstract : Background: IgA vasculitis (IgAV) represents a common systemic vasculitis in paediatric and adult population. Our current knowledge of disease pathogenesis is still very limited and there is no information on miRNAs profile in IgAV. Objectives: The aim of our study was to determine the expression of three miRNAs (miR-148–3p, miR-155–5p and miR-223–3p) in the affected skin of adult IgAV patients. Methods: The study included 65 skin samples from consecutive, untreated IgAV patients (61% male, median age 67.6 years, range 29–91), diagnosed between October 2014 and September 2016, and 10 control skin samples. Total RNA was isolated from tissue section of formalin-fixed, paraffin-embedded samples of biopsied IgAV vasculitic skin lesions and normal skin samples. Expression of miR-148–3p, miR-155–5p and miR-223–3p was measured using qRT-PCR. Skin miRNAs expression was then correlated to clinical characteristics of adult IgAV patients. To present relative miRNA expression the ΔΔCT method was used. Results: We found significantly higher expression levels of miR-223–3p in the affected skin compared to controls (14-fold; p<0.001). The expression of the 148b-3p and miR-155–5p was near normal levels (1.05-fold and 1.13-fold increase, respectively). The differences in the expression of miR-223–3p depending on clinical parameters of IgAV are presented in Table 1 . Patients with necrotic skin lesions had significantly higher miR-223 tissue expression than those with non-necrotic purpura (p=0.020). Gastrointestinal tract (GIT) involvement inversely correlated with the level of skin miR-223 expression (p=0.024). No significant relationship between renal involvement and skin miR-223 was found. Conclusions: miR-223 expression was increased in the affected skin of IgAV in comparison to normal skin. Levels of miR-223 expression correlated with severity of skin involvement and inversely with GIT involvement. Disclosure of Interest: None declared